Criminal track and risk factors of minors who exercise filio-parental violence - Keren Cuervo; Natalia Palanques; Pilar Busquets (Revista Sobre la Infancia y la Adolescencia)
In the last few years, mass media have shown cases of a new kind of a worryingly domestic violence, the child-to-parent violence, which is increasing alarmingly. Thereby, the main objective of this paper is to analyse the criminal career and risk factors of the minors who have committed child-to-parent violence depending on the sex.